Entre o eito da cana e os caminhos da cidade: modos de vida, narrativas e espaços de sociabilidade de trabalhadores de Jaboticabal-SP - Veiga, Olavo Henrique Vieira (2024)
This master's thesis discusses the experiences, social networks, and presence of sugarcane workers in the municipality of Jaboticabal-SP, starting from the 1960s. The main issue guiding this research was to understand how these individuals constituted themselves as workers during the process of urban occupation. Therefore, I focused on analyzing how the ways of life that were in contention during this specific period were imbued with a historicity that defined and shaped these relationships. Thus, I sought to examine how the values, interpretations, and structures set up in this economic dynamic that were observed, identified, and constructed by the individuals themselves influenced their identity as workers. To achieve this, I used oral interviews conducted with the workers, photographs provided by the interviewees, and documents produced by the Municipal Government and statistical institutions to depict the cartography that mark the presence of these individuals in the rural and city.